2020
DOI: 10.1186/s12879-020-05481-x
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood disadvantage and 30-day readmission risk following Clostridioides difficile infection hospitalization

Abstract: Background Clostridioides difficile infection (CDI) is commonly associated with outcomes like recurrence and readmission. The effect of social determinants of health, such as ‘neighborhood’ socioeconomic disadvantage, on a CDI patient’s health outcomes is unclear. Living in a disadvantaged neighborhood could interfere with a CDI patient’s ability to follow post-discharge care recommendations and the success probability of these recommendations, thereby increasing risk of readmission. We hypothesized that neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…We found that patients in the most disadvantaged neighborhoods were more likely to be racial/ethnic minorities, report worse health status, and live alone than those in less disadvantaged neighborhoods. Also, consistent with previous studies on other care settings (Bhavsar et al, 2018; Kind et al, 2014; Nacht et al, 2022; Scaria et al, 2020), we found that patients living in less disadvantaged neighborhoods were associated with better home health outcomes than those in the most disadvantaged neighborhoods. Our findings suggest that, for Medicare beneficiaries, remaining in the community and home through home health care is more challenging in the most disadvantaged neighborhoods than in less disadvantaged neighborhoods.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that patients in the most disadvantaged neighborhoods were more likely to be racial/ethnic minorities, report worse health status, and live alone than those in less disadvantaged neighborhoods. Also, consistent with previous studies on other care settings (Bhavsar et al, 2018; Kind et al, 2014; Nacht et al, 2022; Scaria et al, 2020), we found that patients living in less disadvantaged neighborhoods were associated with better home health outcomes than those in the most disadvantaged neighborhoods. Our findings suggest that, for Medicare beneficiaries, remaining in the community and home through home health care is more challenging in the most disadvantaged neighborhoods than in less disadvantaged neighborhoods.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings align with previous studies on neighborhood context. Several studies have shown that people in more disadvantaged neighborhoods are associated with worse health outcomes than their counterparts in less disadvantaged neighborhoods (Bhavsar et al, 2018; Kind et al, 2014; Nacht et al, 2022; Scaria et al, 2020). For example, Kind and colleagues have shown that living in the most disadvantaged neighborhoods is associated with a higher risk of hospital readmission among Medicare patients discharged with congestive heart failure, pneumonia, or myocardial infarction (Kind et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“… 11 In addition, comorbidities and socioeconomic factors were also considered to be associated with readmission. 12 , 13 So far, readmissions for major disease and surgical diagnoses have been studied, but the risk factors for early unplanned readmission among patients with pulmonary TB without research. Thus, this study aimed to investigate risk factors associated with 31-day unplanned readmission of patients previously discharged with pulmonary TB in China.…”
mentioning
confidence: 99%
“…Approximately 20-27% of all CDI cases are community associated with an incidence rate of 20-30 per 100,000 population across the USA, Europe, and Canada [2]. Patients with recurrent CDI (rCDI) face dire clinical sequelae, including poorer prognosis and higher complication rates [8][9][10][11][12][13]. CDI is rated as an urgent antibiotic threat by the US Centers for Disease Control and Prevention [3].…”
Section: Introductionmentioning
confidence: 99%